APLIKASI THEORY OF PLANNED BEHAVIOUR DAN PERSEPSI RISIKO TERHADAP MINAT BERINVESTASI MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS BRAWIJAYA - I Gusti Ngurah Gotama (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research is to analyze the factors that affect the interests of accounting students to make investments. This study is based on the theory of planned behavior and perceived risk consisting of attitude, subjective norm, perceived behavioral control, and perceived risk. This explanatory research uses a quantitative approach with questionnaire as the data collection method. It was conducted in the Accounting Department of Economics and Business Faculty of Brawijaya University using a purposive sampling method, which obtained 82 respondents. The analysis is performed using multiple regression analysis. The research finds that the factors affecting the interest of accounting student to make investments are attitude, subjective norm, and perceived behavioral control. Perceived risk does not affect the interest of accounting students to make investments. Keywords: attitude, subjective norms, perceived behavioral control, risk perception, interest in investing